Fusobacterium nucleatum and Treponema denticola are robust biomarkers for gingivitis and periodontitis in small dogs - Daehyun Kwon; Daehyun Kwon; Kisuk Bae; Kwangsik Jang; Kwangsik Jang; Hyun Min Jo; Hyun Min Jo; Seong Soo Kang; Seong Soo Kang; Jonghoe Byun; Se Eun Kim; Se Eun Kim (Frontiers in Veterinary Science)
IntroductionPeriodontal disease is one of the most common oral diseases in dogs and humans. It starts with gingivitis, a reversible condition, and progresses to an irreversible condition, periodontitis. Unlike humans, the etiology of periodontal disease in dogs has not been widely studied. Many studies suggest that bacteria strongly implicated in human periodontal disease might also play a role in canine periodontal disease. In contrast to studies examining only the prevalence of bacteria, a recent study analyzed 336 gingival crevicular fluid (GCF) samples in dogs to evaluate the prevalence of 11 putative periodontopathic bacteria and the correlation and association of bacterial numbers individually and in combination with periodontal disease stages. Results showed that Treponema denticola (Td) was a strong prognostic biomarker for periodontitis in dogs. However, a limitation of this study was that samples were grouped according to the periodontal status of the target tooth only, without assessment of the overall oral health. Furthermore, the findings of this study revealed a need for validation in a larger sample size.Materials and methodsThis study ensured that the overall oral health assessment of dogs under 20 kg matched with sampled groups, thus eliminating the influence of environmental factors on the results. Furthermore, 1,054 GCF samples were analyzed using quantitative real-time polymerase chain reaction (qPCR) for 12 bacteria, including the same 11 putative periodontopathic bacteria [Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), Td, Fusobacterium nucleatum (Fn), Prevotella nigrescens (Pn), Prevotella intermedia (Pi), Parvimonas micra (Pm), Eubacterium nodatum (En), Campylobacter rectus (Cr), and Eikenella corrodens (Ec)] and Porphyromonas gulae (P. gulae), suspected to be a major causative agent of periodontitis in dogs in some statistical evaluatioins.ResultsInterestingly, the present study found that Fn was strongly associated with gingivitis and reconfirmed a strong association between Td and periodontitis (irreversible periodontal disease). However, Aa showed no relevance, and P. gulae was not significantly associated with periodontal disease in dogs in this study.ConclusionThese findings suggest that Fn and Td would be robust biomarkers for the severity of periodontal disease in small dogs.